A new species of Endecous Saussure, 1878 (Orthoptera, Gryllidae) from northeast Brazil with the first X(1)X(2)0 chromosomal sex system in Gryllidae - Zefa, Edison; Redue, Darlan Rutz; Matiotti Da Costa, Maria Katia; Fontanetti, Carmem S. [UNESP]; Gottschalk, Marco Silva; Padilha, Giovanna Boff; Silva, Anelise Fernandes E.; Martins, Luciano De P. (Magnolia Press, 2014)
In this paper we describe a new species of Luzarinae cricket collected from the cave Gruta de Ubajara, municipality of Ubajara, State of Ceara, Brazil, highlighting phallic sclerites morphology and chromosome complement as diagnostic characters. We presented meiotic and mitotic characterization in order to define the karyotype with 2n = 12 + X1X2 male/12 + X1X1X2X2 female. This represents the first record of X(1)X(2)0 chromosomal sex system in Gryllidae.
Keywords: insect; Ensifera; Luzarinae; sex chromosome; cave cricket